Condiciones de posibilidad de las atribuciones mentales en la díada humano-inteligencia artificial - José Miguel Biscaia Fernández (Claridades: Revista de Filosofía)
This essay discusses the limits of mental attribution between humans and intelligent machines. Starting from the ontological presuppositions of functionalism and technological transhumanism that a strong Artificial Intelligence (strong-AI) with mental states could be feasible, I analyse the conditions of possibility of mental attribution in first, second and third person perspective between both agents. I conclude that, despite the enormous conceptual debate and the considerable technical difficulties of this undertaking, in case there was a strong-AI with cognitive abilities similar to ours there would be no nomological limits that prevent some kind of bidirectional, asymmetric and gradual mental attribution.